Structural studies on the capsular antigens of some Escherichia coli serotypes - Leslie, Margaret Ruth (Rhodes University, Faculty of Pharmacy, Pharmacy, 1995)
The research presented in this thesis forms part of an on-going collaborative programme concerned with the determination of the chemical structures of the surface antigens of bacteria belonging to genera within the family Enterobacteriaceae. Bacteria of this family are opportunistic pathogens and are frequently responsible for serious infections in animals and man. Surface antigens produced by virulent strains are largely polysaccharides and occur as lipopolysaccharides (the O-antigens) and capsular polysaccharides (the K-antigens) respectively. The extracellular polysaccharide antigens expressed by strains of the species Escherichia coli are of considerable . interest due to their effect on immunological processes and the relationship which exists between their chemical structure and virulence. To date, some seventy-four K-antigens have been distinguished serologically within the species E. coli and structures have been determined for most of these. The K-antigens of E. coli are structurally diverse and exhibit serological cross-reactivity with other pathogenic bacteria. The structures of five previously unstudied E. coli K-antigens, viz. those produced by serotypes 020:K1 01 :H-, 08:K45:H9, 08:K50:H-, 0101 :K1 03:H-, and 08:K43:H11, are presented in this thesis. A variety of chemical techniques has been employed in the structural analysis, and these are discussed. Two-dimensional NMR spectroscopic techniques proved invaluable for the structural elucidation of these complex carbohydrates, and high-field NMR spectroscopy alone was used in the analysis of the K43 antigen. Structural analysis of the K1 03 antigen was facilitated by specific enzymatic degradation, using a bacteriophage-borne endoglycanase. The K45 antigen was found to contain the unusual sugar 3-acetamido-3,6-dideoxygalactopyranose, while the K50 and K103 antigens join a minority group of polysaccharides which contain pyruvate as their only acidic component.
Keywords: Escherichia; Polysaccharides; Antigens; Enterobacteriaceae